2021
DOI: 10.1111/jdv.17098
|View full text |Cite
|
Sign up to set email alerts
|

MEDNIK‐like syndrome due to compound heterozygous mutations in AP1B1

Abstract: 2 Harries MJ, Meyer K, Chaudhry I et al. Lichen planopilaris is characterized by immune privilege collapse of the hair follicle's epithelial stem cell niche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…8 More recently, authors reported a single G insertion in a stretch of 8 consecutive G's between nucleotides 356 and 365 in exon 4, encoding a premature stop codon; these patients had a multisystemic presentation. 9 Interestingly, pathogenic variants, including homozygous deletions 10 and compound heterozygous 11 variants, in another subunit of the adaptor-related protein complex, AP1B1, can also present with a IDEDNIK-like syndrome with ichthyosis, enteropathy, and developmental delay. These syndromes fall into the group of epithelial structure, trafficking, and polarity according to the most recent classification of monogenic intestinal epithelial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…8 More recently, authors reported a single G insertion in a stretch of 8 consecutive G's between nucleotides 356 and 365 in exon 4, encoding a premature stop codon; these patients had a multisystemic presentation. 9 Interestingly, pathogenic variants, including homozygous deletions 10 and compound heterozygous 11 variants, in another subunit of the adaptor-related protein complex, AP1B1, can also present with a IDEDNIK-like syndrome with ichthyosis, enteropathy, and developmental delay. These syndromes fall into the group of epithelial structure, trafficking, and polarity according to the most recent classification of monogenic intestinal epithelial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…, 2019 ; Boyden et al. , 2019 ; Ito et al. , 2021 ) subunits, however, do have skin manifestations, probably owing to the requirement of AP-1 for polarized sorting in epithelial cells ( Fölsch et al.…”
Section: Discussionmentioning
confidence: 99%